2016
DOI: 10.1016/j.healthplace.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Dying younger in Scotland: Trends in mortality and deprivation relative to England and Wales, 1981–2011

Abstract: Given previous evidence that not all Scotland's higher mortality compared to England & Wales (E&W) can be explained by deprivation, the aim was to enhance understanding of this excess by analysing changes in deprivation and mortality in Scotland and E&W between 1981 and 2011. Mortality was compared by means of direct standardisation and log-linear Poisson regression models, adjusting for age, sex and deprivation. Different measures of deprivation were employed, calculated at different spatial scales. Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…The 9% excess for Scotland compared with England and Wales is lower than that observed by Popham and Boyle3 for the same age group (probably explained by the incorporation of additional socioeconomic controls and differences in the sample and length of follow-up period), but similar to that observed for all ages in analyses by Hanlon et al 1 for 2001 (8%) and Schofield et al 13 for 2011 (10%). The 27% higher mortality in Glasgow compared with Liverpool and Manchester is also comparable to the analyses based on area-based measures of income deprivation (30% higher mortality for age <65 years) 9…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The 9% excess for Scotland compared with England and Wales is lower than that observed by Popham and Boyle3 for the same age group (probably explained by the incorporation of additional socioeconomic controls and differences in the sample and length of follow-up period), but similar to that observed for all ages in analyses by Hanlon et al 1 for 2001 (8%) and Schofield et al 13 for 2011 (10%). The 27% higher mortality in Glasgow compared with Liverpool and Manchester is also comparable to the analyses based on area-based measures of income deprivation (30% higher mortality for age <65 years) 9…”
Section: Discussionsupporting
confidence: 61%
“…Suicide has been shown to make a considerable contribution to the high levels of excess mortality observed Scotland and Glasgow 6 9 13…”
Section: Introductionmentioning
confidence: 99%
“…Much of this is explained by recent experiences of deindustrialisation, deprivation and poverty, the latter being root causes of poor health in all societies, not just Scotland 4,[8][9][10][11][12] . However, in addition, high levels of excess mortality -that is, higher mortality over and above that explained by differences in socioeconomic deprivation -have been observed for Scotland compared with England & Wales [13][14][15][16][17] , as well as for Glasgow compared with similar post-industrial UK cities such as Liverpool,…”
Section: Introductionmentioning
confidence: 99%
“…These suggest some upward trend in prescriptions for certain types of mental illness in the period since 2006 (McTaggart, personal communication, 2016) and comments on how prescription patterns vary according to socio-demographic factors like gender and age (Francis and McTaggart, 2015). It has also been reported (Schofield et al, 2016) that, compared with England and Wales, Scotland has shown a growing excess mortality due to self-harm, allowing for differences in deprivation, and Scottish policies have sought to protect mental health care provision against austerity cuts. It is recognized that more evidence is needed to quantify the nature of the relationship between employment during economic recession and health in the population.…”
Section: Background To the Researcha Review Of Existing Evidencementioning
confidence: 99%